Effects of extracellular adhesion molecules on immune cell mediated solid tumor cell killing - Kim, Seong-Eun; Yun, Suji; Doh, Junsang (Frontiers in Immunology, 2022)
Adoptive cell therapy (ACT) using ex vivo engineered/expanded immune cells demonstrated poor efficacy against solid tumors, despite its great success in treating various hematopoietic malignancies. To improve ACT for solid tumors, it is crucial to comprehend how the numerous components of the tumor microenvironment (TME) surrounding solid tumor cells influence killing ability of immune cells. In this study, we sought to determine the effects of extracellular adhesion provided by extracellular matrix (ECM) of TME on immune cell cytotoxicity by devising microwell arrays coated with proteins either preventing or promoting cell adhesion. Solid tumor cells in bovine serum albumin (BSA)-coated microwells did not attach to the surfaces and exhibited a round morphology, but solid tumor cells in fibronectin (FN)-coated microwells adhered firmed to the substrates with a flat shape. The seeding densities of solid tumor cells and immune cells were tuned to maximize one-to-one pairing within a single microwell, and live cell imaging was performed to examine dynamic cell-cell interactions and immune cell cytotoxicity at a single cell level. Both natural killer (NK) cells and T cells showed higher cytotoxicity against round tumor cells in BSA-coated microwells compared to flat tumor cells in FN-coated microwells, suggesting that extracellular adhesion-mediated firm adhesion of tumor cells made them more resistant to immune cell-mediated killing. Additionally, NK cells and T cells in FN-coated microwells exhibited divergent dynamic behaviors, indicating that two distinct subsets of cytotoxic lymphocytes respond differentially to extracellular adhesion cues during target cell recognition.